2019
DOI: 10.1177/2050312119871785
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of left ventricle ejection fraction and early in-hospital mortality in patients with ST-segment elevation myocardial infarction: Single-center data from a tertiary referral university hospital in Istanbul

Abstract: Background: Little is known about the management and mortality rates of ST-segment elevation myocardial infarction patients in developing countries. In this study, to expose independent predictors of early (24 h) in-hospital mortality and ejection fraction, we report our experience with 362 ST-segment elevation myocardial infarction patients admitted to the Istanbul Medical Faculty, Istanbul University, a tertiary referral university hospital, and treated with primary percutaneous intervention. Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Chehab et al [ 28 ] demonstrated that patients with acute MI and reduced EF (< 35%) developed higher in-hospital mortality. According to Emet et al’s [ 29 ] studies in Istanbul, there was a significant association between mean LVEF and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Chehab et al [ 28 ] demonstrated that patients with acute MI and reduced EF (< 35%) developed higher in-hospital mortality. According to Emet et al’s [ 29 ] studies in Istanbul, there was a significant association between mean LVEF and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%